2016
DOI: 10.1002/pbc.26091
|View full text |Cite
|
Sign up to set email alerts
|

Increased rates of body dissatisfaction, depressive symptoms, and suicide attempts in Jamaican teens with sickle cell disease

Abstract: Jamaican adolescents with SCD have significantly higher rates of negative body satisfaction and depressive symptoms, and nearly twice the rate of attempted suicide, compared with their healthy peers. This underscores the need for healthcare professionals to better explore and discuss healthy weight, body satisfaction, and coping with the demands and uncertainties of having a chronic illness with Jamaican adolescents with SCD, even while promoting body acceptance and good self-esteem. Screening for mood disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“… 57 - 59 Past studies in our adolescents have reported that being in school seems to be a resiliency factor and appears to be protective against risky behaviors and depressive symptoms. 25 , 29 As adolescents become adults, higher educational attainment will also afford them better employment opportunities and hence improve their self-management capabilities. 57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 - 59 Past studies in our adolescents have reported that being in school seems to be a resiliency factor and appears to be protective against risky behaviors and depressive symptoms. 25 , 29 As adolescents become adults, higher educational attainment will also afford them better employment opportunities and hence improve their self-management capabilities. 57 …”
Section: Discussionmentioning
confidence: 99%
“… 27 They face multiple psychosocial problems such as depression, poorer QOL, social isolation, and maladjustments. 28 - 33 This is the time when they face challenges as they transition their health care from pediatric to adult care and become more independent in managing their disease. 34 - 37 …”
Section: Introductionmentioning
confidence: 99%
“…Individuals with SCD face many obstacles to receiving care; but stigma is one of the most influential and ominous. People who have SCD may experience health-related stigma for a variety of reasons including race, disease status, socioeconomic status, delayed growth and puberty, and/or having chronic and acute pain that needs to be managed with opioids (Bediako & Moffitt, 2011; Bhatt-Poulose, James, Reid, Harrison, & Asnani, 2016; Haywood, Tanabe, Naik, Beach, & Lanzkron, 2013; Lazio et al, 2010; Penner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…2,60 As the psychological and neurobiological sequelae of chronic physical illness are increasingly recognized, the contribution from mental health care providers to medically ill pediatric patients is being increasingly recognized and formalized, particularly among certain illnesses, such as pediatric cancers, epilepsy, cystic fibrosis, and sickle cell disease. [60][61][62][63] For instance, the Cystic Fibrosis Foundation and European Cystic Fibrosis Society recently partnered to produce consensus guidelines on implementing developmentally appropriate psychoeducation and screening for anxiety and depression in cystic fibrosis patients and their caregivers, as well as recommendations for specific treatments, such as cognitive behavioral therapy, selective serotonin reuptake inhibitor medications, and benzodiazepines. 64 Kazak and colleagues composed a recent literature review demonstrating the need for routine, systematic assessments of psychosocial needs in children and caregivers with cancer, 65 while the international Posterior Fossa Society determined in a recent consensus meeting that identification and treatment of emotional and behavioral morbidities in this population is an important avenue for upcoming work.…”
Section: Considerations In Medically Ill Childrenmentioning
confidence: 99%